204k views
5 votes
Y=3x-4x+2y=-3solve using the substation method

User Sundowner
by
4.8k points

1 Answer

3 votes

In this case, we'll have to carry out several steps to find the solution.

Step 01:

Data

y = 3x - 4 eq.1

x + 2y = -3 eq.2

x = ?

y = ?

Step 02:

Substitution method

eq.1 in eq.2

x + 2(3x - 4) = -3

x + 6x - 8 = - 3

7x = -3 + 8

x = 5 / 7

eq.1

y = 3 (5 / 7) - 4

y = 15 / 7 - 4

y = (15 - 28 ) / 7

y = - 13 / 7

The answer is:

x = 5 / 7

y = - 13 / 7

User Dinesh Pandiyan
by
4.5k points